Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531730
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents of remix

Abstract: Reuse of the works of others has become common practice on the Internet and has formed the basis for collaboration in some online communities. However, some works are reused much more frequently than others. In this article we build a quantitative model that explains which factors are most salient in determining the likelihood that an author's work will be reused. Controlling for common factors, such as the work's popularity, we show that the probability of reuse depends on (a) the degree of derivativity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 33 publications
6
35
2
Order By: Relevance
“…Regarding author-related hypotheses, prior research on both OSS (e.g., [28]) and arts communities (e.g., [6,16]) highlighted that authors' prominence and their social embeddedness are antecedents of success. Hence, we expect that content generated by community members with a high status is reused more often.…”
Section: Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding author-related hypotheses, prior research on both OSS (e.g., [28]) and arts communities (e.g., [6,16]) highlighted that authors' prominence and their social embeddedness are antecedents of success. Hence, we expect that content generated by community members with a high status is reused more often.…”
Section: Hypothesesmentioning
confidence: 99%
“…Similar findings are reported by Settles and Dow [22] who analyzed the music community of FAWM and found that the prior exchange of direct messages between musicians is the factor that contributes the most to the successful completion of their collaborations. Hill and Monroy-Hernández [13] performed a study on the success of video animations in Scratch and found that the likelihood of engendering derivative works is related to cumulativeness (i.e., remixes themselves are reused more than de novo content), which is in direct contrast with the finding by Cheliotis et al [6] on the degree of derivativity (i.e., the 'newer' the content, the higher the likelihood of remix). The contrasting findings from these two works provide additional motivation to further study the antecedents of artifact reuse in collaborative songwriting communities.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Driven by the advent of open platforms and communities on the internet, it has only been in recent years that the concept of innovation through recombination has gained further attention (Lessig, 2008;Khatib et al, 2011;Tuite and Smith, 2012;Cheliotis et al, 2014;Sapsed and Tschang, 2014;Oehlberg et al, 2015;Dasgupta et al, 2016;Stanko, 2016). Online platforms with openly licensed content and data make it increasingly easy to share and access a wide range of usergenerated ideas (Lee et al, 2010;Kane and Ransbotham, 2012;Leonardi, 2014;Payton, 2016).…”
Section: Introductionmentioning
confidence: 99%